PEMBERDAYAAN KADER REMAJA UNIT KESEHATAN SEKOLAH BERBASIS EDUGAME MOLECULER DALAM MENINGKATKAN KESADARAN BAHAYA KANKER DI SURABAYA - Muhamad Ridlo; Nurullia Hanum Hilfida; Evy Wulandari; Nur Florenty Rehulina Ginting; Ibnaty Salsabila Lirabbiha; Syahda Awwaliyah Mullah Yanurrah; Rizky Artika Ningtyas; Anindya Aurellia Ardianto Putri; Anggita Nova Adinaya (Universitas Muhammadiyah Kudus, 2026)
AbstractCancer is one of the leading causes of mortality worldwide, including in Indonesia, necessitating promotive and preventive interventions from an early age. However, adolescents’ awareness of cancer remains low due to limited access to engaging and comprehensible information. This community service program aimed to enhance adolescents’ knowledge and awareness of cancer through the empowerment of School Health Unit (UKS) cadres using molecular edugame media. The activity was conducted at SMP Negeri 40 Surabaya and SMP IT Ustman Bin Affan from June until October 2025, involving 50 UKS adolescent cadres selected through total sampling. An educational-participatory approach was applied, utilizing molecular edugames Monocancer, Word Puzzle Game, and Flash Cards as the primary learning instruments. Data were collected using pre- and post-tests to measure knowledge improvement and observation to evaluate participation and media effectiveness. The findings demonstrated a significant increase in participants’ knowledge and awareness of cancer, with 60% achieving a high level, 30% a moderate level, and 10% a low level. These results indicate that molecular edugames are effective, interactive tools for adolescent cancer education. The program concludes that educational games represent an innovative strategy for school-based health promotion and recommends broader adoption through collaboration among schools, health professionals, and communities.